2015
DOI: 10.1111/ecc.12396
|View full text |Cite
|
Sign up to set email alerts
|

Development and usability testing of a web-based self-management intervention for oral cancer survivors and their family caregivers

Abstract: Oral cancer (OC) survivors experience debilitating side effects that affect their quality of life (QOL) and that of their caregivers. This study aimed to develop and evaluate a dyadic, web-based intervention to improve survivor self-management and survivor/caregiver QOL. A qualitative needs assessment (semi-structured interviews) with 13 OC survivors and 12 caregivers was conducted to discern information and support needs as well as preferences regarding website features and tools. Results using Grounded Theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 50 publications
2
113
0
3
Order By: Relevance
“…Previous studies have focused on examining the usability or efficacy of eHealth systems. 26,27 In our study, patients and caregivers identified components for DS helpful. Advances in health information technology and increased use of patient portals make it possible to integrate patient preferences for DS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have focused on examining the usability or efficacy of eHealth systems. 26,27 In our study, patients and caregivers identified components for DS helpful. Advances in health information technology and increased use of patient portals make it possible to integrate patient preferences for DS.…”
Section: Discussionmentioning
confidence: 88%
“…This is the first study to our knowledge that explored patient perspectives about which components of DS would be desirable for enhancing communication with clinicians. Previous studies have focused on examining the usability or efficacy of eHealth systems . In our study, patients and caregivers identified components for DS through the use of eHealth and non‐eHealth systems.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, following our findings in relation to financial resources, intervention components relating to financial management [eg,] may be beneficial for HNC survivors. Because of potential issues of accessibility to services, eHealth self‐management interventions may also be of particular value to this population [eg] . Finally, routine screening for QoL needs (eg, using the Patient Concerns Inventory) may help to identify those who need to be targeted with structured supported self‐management programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Through this turmoil the EJCC will continue to place a high value on pan-European (and, indeed, international) Oral cancer is linked to tobacco and alcohol consumption; it is a condition for which we do not routinely screen in most western countries-despite the existence of identifiable pre-cancerous lesions, there is little evidence to date that screening can reduce mortality from this condition. Nevertheless, awareness of early symptoms is important, as is information on self-management strategies for oral cancer survivors, who often live with significant morbidity including facial disfigurement; Badr et al (2016) demonstrate some interesting findings through use of a web-based strategy targeting both oral cancer patients and their family caregivers. Finally, take a look at Hamilton and Thomas's (2016) paper on the experiences of patients with lymphoedema-a condition which can be associated with significant morbidity and distress in cancer patients.…”
Section: The Eu and Cancer Researchmentioning
confidence: 94%
“…Nevertheless, awareness of early symptoms is important, as is information on self‐management strategies for oral cancer survivors, who often live with significant morbidity including facial disfigurement; Badr et al. () demonstrate some interesting findings through use of a web‐based strategy targeting both oral cancer patients and their family caregivers. Finally, take a look at Hamilton and Thomas's () paper on the experiences of patients with lymphoedema—a condition which can be associated with significant morbidity and distress in cancer patients.…”
mentioning
confidence: 99%